Letter (copy) : Jose Rodriguez Vega - Citrine, Walter, 1887-1983
012b-0007-001 International WMC/AC/468 18th [20th] September, 1939. M. R. Lamoneda, Partido Socialista Obrero Español, C/o Parti Socialist Français, 12, City Malesherbes, PARIS IXe. Dear Mr. Lamoneda, JOSE RODRIGUEZ VEGA. With further reference to your letter of 4th September, about the danger which our colleague Jose Rodriguez Vega is facing, we have now heard from the authorities that the question has been brought to the notice of the British Ambassador in Spain. We have been warned that great difficulties are in the way of intervention on his port with the present Spanish Government, but we nave an assurance that he will do what he can to help our friend. If we hear anything further, we shall immediately get in touch with you, you may be sure. Yours sincerely, General Secretary 292/946/12b/7